2015
DOI: 10.1021/acsami.5b03254
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured 2D Diporphyrin Honeycomb Film: Photoelectrochemistry, Photodegradation, and Antibacterial Activity

Abstract: Surface patterns of well-defined nanostructures play important roles in fabrication of optoelectronic devices and applications in catalysis and biology. In this paper, the diporphyrin honeycomb film, composed of titanium dioxide, protoporphyrin IX, and hemin (TiO2/PPIX/Hem), was synthesized using a dewetting technique with the well-defined polystyrene (PS) monolayer as a template. The TiO2/PPIX/Hem honeycomb film exhibited a higher photoelectrochemical response than that of TiO2 or TiO2/PPIX, which implied a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…The honeycomb films formed by organic-inorganic hybrids possess the properties of both organic and inorganic parts, showing potential applications in many fields: electrochemistry [ 117 ], antibacterial treatment [ 118 ], photoelectric devices [ 119 , 120 ], separation [ 121 ], sensors [ 122 ], functional membranes (fluorescent, super-hydrophobic, SERS) [ 98 , 99 , 100 , 114 , 123 ], catalysis [ 99 , 100 ] and so on, as summarized in Figure 17 . The honeycomb films formed by surfactant-modified Au or Ag nanoparticles could be used as the substrate of surface-enhanced Raman spectroscopy (SERS) [ 73 , 99 , 123 ].…”
Section: Organic-inorganic Hybrids As Building Units To Form Honeymentioning
confidence: 99%
“…The honeycomb films formed by organic-inorganic hybrids possess the properties of both organic and inorganic parts, showing potential applications in many fields: electrochemistry [ 117 ], antibacterial treatment [ 118 ], photoelectric devices [ 119 , 120 ], separation [ 121 ], sensors [ 122 ], functional membranes (fluorescent, super-hydrophobic, SERS) [ 98 , 99 , 100 , 114 , 123 ], catalysis [ 99 , 100 ] and so on, as summarized in Figure 17 . The honeycomb films formed by surfactant-modified Au or Ag nanoparticles could be used as the substrate of surface-enhanced Raman spectroscopy (SERS) [ 73 , 99 , 123 ].…”
Section: Organic-inorganic Hybrids As Building Units To Form Honeymentioning
confidence: 99%
“…It has already been observed that anionic porphyrin and TPPS 4itself can bind to DNA externally [46] and, under conditions of high dye concentration, form J-aggregates [47]. Table 1 collects the results of data analyses according to equation (2) relevant to the very first part of the graphs (final part of titration, high C P ).…”
Section: Dna Bindingmentioning
confidence: 99%
“…Porphyrins and porphyrin-based pigments are molecules known since very long time but that are still object of very high interest in cutting-edge research [1][2][3][4][5]. Sulphonatophenyl porphyrins are used as catalysts [6] and photo-catalysts [7], as sensors for analytical purposes [8,9] and in photodynamic therapy [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Recentp rogress has been focused on furthere xpanding the field from fundamental researcht oe ncouraging industrialized applications by the productiono fl arge-area honeycomb structures. [23][24][25][26][27] The films containing honeycombs tructures with varying sizes and morphologies have been successfully used as molecular sieves, [28] sensors, [29] superhydrophobic coatings, [30] antibacterial surfaces, [31] cell culture reservoirs, [32] and templates for electrodeposition of Au or Ag particlesfor surface-enhanced Ramanscattering (SERS). Up to now,v arious candidates have been explored to form honeycomb structures.B esides polymers with diversec ompositions and structures, [12][13][14][15] av ariety of materials with attractive properties have also been tried, including carbon nanotubes( CNTs), [16,17] grapheneo xide (GO), [18] proteins, [19] small organic molecules, [20][21][22] and inorganic-organic hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now,v arious candidates have been explored to form honeycomb structures.B esides polymers with diversec ompositions and structures, [12][13][14][15] av ariety of materials with attractive properties have also been tried, including carbon nanotubes( CNTs), [16,17] grapheneo xide (GO), [18] proteins, [19] small organic molecules, [20][21][22] and inorganic-organic hybrids. [23][24][25][26][27] The films containing honeycombs tructures with varying sizes and morphologies have been successfully used as molecular sieves, [28] sensors, [29] superhydrophobic coatings, [30] antibacterial surfaces, [31] cell culture reservoirs, [32] and templates for electrodeposition of Au or Ag particlesfor surface-enhanced Ramanscattering (SERS). [33,34] Polyoxometalates (POMs) are ab ig class of polyanions which consist of early transition metals in their highest oxidation states.…”
Section: Introductionmentioning
confidence: 99%